2014
DOI: 10.1111/opn.12053
|View full text |Cite
|
Sign up to set email alerts
|

Can therapy dogs evoke awareness of one's past and present life in persons with Alzheimer′s disease?

Abstract: Background Persons with Alzheimer's disease (AD) sometimes express themselves through behaviours that are difficult to manage for themselves and their caregivers, and to minimise these symptoms alternative methods are recommended. For some time now, animals have been introduced in different ways into the environment of persons with dementia. Animal‐Assisted Therapy (AAT) includes prescribed therapy dogs visiting the person with dementia for a specific purpose. Aim This study aims to illuminate the meaning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
78
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(78 citation statements)
references
References 34 publications
0
78
0
Order By: Relevance
“…Several studies [13,16,17,20,21,23,24,34,35] suggest that AAT with a therapy dog influences persons with AD and other dementias in many ways, for example creating increased social activity, joy and well-being, although Kongable et al [36] found that when a therapy dog moved in to the ward with persons with AD, no significant increases of social behaviour was noted. Swall, Ebbeskog, Lundh Hagelin and Fagerberg [37] also found that the presence of a therapy dog brings moments of sadness difficult for persons with AD to handle. In the present study, we studied activity as a form of effects, which also followed the prescriptions of the AAT.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies [13,16,17,20,21,23,24,34,35] suggest that AAT with a therapy dog influences persons with AD and other dementias in many ways, for example creating increased social activity, joy and well-being, although Kongable et al [36] found that when a therapy dog moved in to the ward with persons with AD, no significant increases of social behaviour was noted. Swall, Ebbeskog, Lundh Hagelin and Fagerberg [37] also found that the presence of a therapy dog brings moments of sadness difficult for persons with AD to handle. In the present study, we studied activity as a form of effects, which also followed the prescriptions of the AAT.…”
Section: Discussionmentioning
confidence: 96%
“…The case study is a part of a larger longitudinal research project following persons with AD over a period of 6 months where AAT with a therapy dog team is used [37] . Data for the present study was gathered over a period of 16 weeks between February and September 2011.…”
Section: Methodsmentioning
confidence: 99%
“…The VIOs from the sessions were viewed and transcribed into text without interpretation (Swall et al, 2014). The transcribed texts were then separated from the VIOs and, according to Ricoeur (1976), the text then “stands on its own”.…”
Section: Methodsmentioning
confidence: 99%
“…However, the presence of a therapy dog could also induce reactions such as agitation (Filan & Llewellyn‐Jones ), or a sadness that is difficult to handle (Swall et al . ). Despite some negative aspects of therapy dog visits to persons with dementia, AAT is commonly used with the specific purpose of improving their situation.…”
Section: Introductionmentioning
confidence: 97%